Leisure and Positive Psychology - Stebbins, Robert A. author. aut Link
VI, 156 p.
Keywords: This book explores, from a leisure studies perspective, the central role that leisure has to play in positive psychology, exploring themes such as flow, fulfilment, altruism, well-being, and interpersonal relationships.